COVID-19 and pro-sociality: How do donors respond to local pandemic severity, increased salience, and media coverage? - Maja Adena; Julian Harke (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2021)
Has the COVID-19 pandemic affected pro-sociality among individuals? After the onset of the pandemic, many charitable appeals were updated to include a reference to COVID-19. Did donors increase their giving in response to such changes? In order to answer these questions, we conducted a real-donation online experiment with more than 4,200 participants from 149 local areas in England and over 21 weeks. First, we varied the fundraising appeal to either include or exclude a reference to COVID-19. We found that including the reference to COVID-19 in the appeal increased donations. Second, in a natural experiment-like approach, we studied how the relative local severity of the pandemic and media coverage about local COVID-19 severity affected giving in our experiment. We found that both higher local severity and more related articles increased giving of participants in the respective areas. This holds for different specifications, including specifications with location fixed effects, time fixed effects, a broad set of individual characteristics to account for a potentially changing composition of the sample over time and to account for health- and work-related experiences with and expectations regarding the pandemic. While negative experiences with COVID-19 correlate negatively with giving, both approaches led us to conclude that the pure effect of increased salience of the pandemic on pro-sociality is positive. Despite the shift in public attention toward the domestic fight against the pandemic and away from developing countries' challenges, we found that preferences did not shift toward giving more to a national project and less to developing countries.
Keywords: C93; D64; D12; 330; COVID-19; charitable giving; online experiments; natural experiments